THE EFFECT OF INTERVAL TRAINING ON ENDURANCE OF WOMEN’S VOLLEYBALL ATHLETES AT CLUB SEMPANA DURI - Miswarizal, Nurul octania putry; Vai, Aref; Sulastio, Agus (Journal Sport Science Indonesia, 2023)
The problem in this research is the lack of endurance of athletes during training and in competitions. The purpose of this study was to determine the effect of interval training on the endurance of female volleyball athletes at the Sempana Duri club. The population in this study were all female volleyball athletes at the Sempana Duri club using a total sampling technique of 10 people. This type of research is, using a one-group pre-test-post-test design. From the results of this study, it can be concluded that the athletes obtained an average post-test result of 23.59, based on the pretest LoMaks normality test of 0.0793 <L table 0.258, and posttest LoMaks 0.1106 <L table 0.258 said to be normal. based on the statistical analysis of the t test, the different values ​​obtained are 1.18 and produce tcount of 11.8 and ttable of 1.833. Means tcount > ttable. It can be concluded that interval training (X) has an effect on endurance (Y) in female volleyball athletes at the Sempana Duri club.